Modernization Of Social And Political Life In Uzbekistan - Ibodulla Kungirov (Peerian Journals Publishing, 2023)
Today, in a situation where globalization has a direct impact on all spheres of society's life, the main attention is paid to the processes of national spirituality, awareness of national identity, spiritual revival, and spiritual growth. Modernization processes in the spiritual sphere of society's life are manifested in the form of the harmony of national and universal values, the interaction of different cultures and the enrichment of each other, the introduction of innovations and discoveries in the field of culture and art, science into our spiritual life and further enriching it.
Keywords: Modernization; globalization